The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/art.40903
|View full text |Cite
|
Sign up to set email alerts
|

Selective Sexual Dimorphisms in Musculoskeletal and Cardiopulmonary Pathologic Manifestations and Mortality Incidence in the Tumor Necrosis Factor–Transgenic Mouse Model of Rheumatoid Arthritis

Abstract: Objective To examine and quantify the sexual dimorphism in pathologic features manifested in the musculoskeletal and cardiopulmonary systems and incidence of mortality in the tumor necrosis factor–transgenic (TNF‐Tg; Tg3647 strain) mouse model of inflammatory erosive arthritis. Methods Kaplan‐Meier survival estimates were determined in male and female Tg3647 mice and sex‐matched wild‐type (WT) littermate mice. Longitudinal and cross‐sectional pathologic outcomes in the musculoskeletal and cardiopulmonary syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 52 publications
3
59
1
Order By: Relevance
“…All studies were performed with littermate wild-type or iNOS −/− controls. Due to the observed temporal differences in male and female TNF-Tg pathology [11], male and female animals were studied at different ages to match disease phenotype. Longitudinal analysis (ultrasound and near-infrared lymphatic imaging) was performed in female mice at 2, 3, and 4 months of age and in male mice at 3, 4, 5, and 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies were performed with littermate wild-type or iNOS −/− controls. Due to the observed temporal differences in male and female TNF-Tg pathology [11], male and female animals were studied at different ages to match disease phenotype. Longitudinal analysis (ultrasound and near-infrared lymphatic imaging) was performed in female mice at 2, 3, and 4 months of age and in male mice at 3, 4, 5, and 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Histology and micro-computed tomography analyses show that severe knee synovitis and bone erosion do not occur until the PLN collapses, indicating PLN collapse is a biomarker for severe knee arthritis [7, 8, 10]. Importantly, all of these studies were performed in male mice, but when we investigated female mice, we found significantly altered progression indicating that in the TNF-Tg mouse model, these lymphatic and arthritis phenotypes are sexually dimorphic [11]. Female mice show an earlier peak expansion (~ 4 months of age) and collapse (~ 6 months of age) of their popliteal lymph node concomitant with earlier starting synovitis and bone erosions (3 months of age).…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on the synovial lymphatic system during arthritic progression and flare (10,12,16,20,25,26,35,43,44), and the effects of interventions that specifically target lymphatic contractions, whose physiologic importance in supporting lymphatic drainage and subsequent onset of lymphedema have been established in preclinical and clinical studies (7,29,45,46). We have also performed transmission electron microscopy studies on WT, Expanding and Collapsed PLVs (42).…”
Section: Discussionmentioning
confidence: 99%
“…We have also recently demonstrated that PLN expansion during arthritic progression is dependent on iNOS by longitudinally monitoring PLN volumes with PD-US in TNF-Tg versus TNF-Tg x iNOS -/mice (25). Global ablation of iNOS preserved PLV contraction frequency assessed by in vivo NIR-ICG imaging, which was associated with significantly reduced synovitis in female TNF-Tg mice that typically exhibit an accelerated disease course (25,26). Thus, the specific features associated with nitric oxide signaling and PLV contractility in TNF-Tg mice warrants further investigation.…”
Section: Introductionmentioning
confidence: 91%
“…The lymphatic system provides homeostatic turnover of interstitial fluid and trafficking of immune cells to the closest lymph node (4,5). Multiple studies on murine RA models have demonstrated dramatic changes in both lymphatic vessel (LV) contractions and the joint-draining lymph node volume with disease progression (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). During the early and middle phases of musculoskeletal inflammation, the joint-draining lymph node undergoes a rapid increase in volume to several fold greater than unaffected lymph nodes.…”
Section: Introductionmentioning
confidence: 99%